2016
DOI: 10.1016/j.bpj.2016.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Multisite Phosphorylation Modulates the T Cell Receptor ζ-Chain Potency but not the Switchlike Response

Abstract: Multisite phosphorylation is ubiquitous in cellular signaling and is thought to provide signaling proteins with additional regulatory mechanisms. Indeed, mathematical models have revealed a large number of mechanisms by which multisite phosphorylation can produce switchlike responses. The T cell antigen receptor (TCR) is a multisubunit receptor on the surface of T cells that is a prototypical multisite substrate as it contains 20 sites that are distributed on 10 conserved immunoreceptor tyrosine-based activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 64 publications
8
47
2
Order By: Relevance
“…S7B). Kinetic proofreading can be realized by a number of different molecular mechanisms, such as sequential or random phosphorylation of the TCR (54,55) and/or the recruitment of Lck-associated coreceptors (56) (SI Appendix, Fig. S7A).…”
Section: Fig 4 Systematic Analyses Of Signaling Models Reveals Thatmentioning
confidence: 99%
“…S7B). Kinetic proofreading can be realized by a number of different molecular mechanisms, such as sequential or random phosphorylation of the TCR (54,55) and/or the recruitment of Lck-associated coreceptors (56) (SI Appendix, Fig. S7A).…”
Section: Fig 4 Systematic Analyses Of Signaling Models Reveals Thatmentioning
confidence: 99%
“…The strength of this approach is the ability to model with very few assumptions, therefore the qualitative features of our conclusions are expected to be robust to atomistic and chemical details. We anticipate that approaches similar to ours will help reveal complex molecular behavior for other systems, for example cooperativity of binding to unstructured domains of signaling molecules [Mukhopadhyay et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely appreciated that multiple ITAMs contribute to signal amplification with some evidence that they preferentially contribute to enable amplification at low antigen doses . Mathematical models have previously suggested that multiple ITAMs may be important for generating switch‐like responses by various mechanisms, but experimental work has failed to observe this …”
Section: Mechanisms Of T‐cell Sensitivity To Antigenmentioning
confidence: 99%